ANALISIS PENDAPATAN FAKTOR-FAKTOR PRODUKSI USAHATANI SEMANGKA DI LAHAN GAMBUT DESA PALINGKAU SEJAHTERA KECAMATAN KAPUAS MURUNG KABUPATEN KAPUAS - Setiya Dewi Purwanti; Betrixia Barbara; Trisna Anggreini (J-SEA (JOURNAL SOCIO ECONOMIC AGRICULTURAL), 2019)
The research is aimed to determined the cost of production, income, revenue, and profit. The research was conducted from July 2018 to January 2019. The method used the sensus method and used in determining the location was purposive. The samples used were 40 watermelon farmers. The total average cost production of farming watermelon Rp. 15.599.004 per growing season, with income Rp. 24.592.500, the average revenue Rp. 13.182.746, and the average profit Rp. 8.993.496 per growing season.